FORMULATION AND OPTIMIZATION OF A GALLIC ACID-LOADED NAIL SERUM USING FACTORIAL DESIGN FOR ENHANCED NAIL DELIVERY - LOBO, JANE GLENISHA; SALDANHA, JOEL SYLVESTER; POLALI, DIYA; CARMEL, JENITTA MARIA; MADHAVA, ASHWINI (International Journal of Applied Pharmaceutics, 2025)
Objective: Onychomycosis is a persistent fungal infection of the nails, and conventional treatments, including oral antifungals, are often associated with systemic side effects, such as hepatotoxicity, and exhibit high recurrence rates. In response to these challenges, the present project aimed to develop a novel gallic acid-loaded nail serum, a unique approach that leverages the antifungal, antioxidant, and anti-inflammatory properties of gallic acid to formulate a safer and more efficacious topical treatment than conventional therapy. Methods: The formulations were developed using a 2³ factorial design approach to optimize the concentrations of acetone, ethyl acetate, and glycerol for desired viscosity and spreadability. The serum was evaluated for its physical characteristics, viscosity, spreadability, in vitro drug permeation, antifungal activity, and in vitro cytocompatibility using the MTT assay on L929 fibroblast cells, as well as its ex vivo efficacy in a porcine hoof model. Results: The optimized formulation showed appropriate viscosity (755.67 cP) and spreadability (7.22 cm), along with smooth texture, good gloss, and a pH suitable for nails (pH 5.2–5.4). Drug permeation studies revealed that the serum enhanced gallic acid penetration more than an aqueous solution. Antifungal studies showed a better zone of inhibition (22.0±0.5 mm) compared to a marketed antifungal product. Cytocompatibility studies indicated more than 88% cell viability. Ex vivo analysis confirmed significant fungal clearance on infected hoof models. Conclusion: The gallic acid-loaded nail serum developed in this study demonstrated effective antifungal activity, enhanced nail penetration, and favorable physical properties, It offers a natural, safe, and patient-friendly alternative to conventional antifungal treatments for onychomycosis, encouraging further clinical research and potential commercial development.